2018
DOI: 10.1021/acsmacrolett.7b01001
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Step-Growth Polymerization of AB-Type Photo-Monomers at Ambient Temperature

Abstract: We introduce two AB-type monomers able to undergo a facile catalyst-free photoinduced polycycloaddition of photocaged dienes, enabling rapid Diels–Alder ligations under UV-irradiation (λmax = 350 nm) at ambient temperature, closely adhering to Carother’s equation established by a careful kinetic study (17800 g mol–1 < M w < 24700 g mol–1). The resulting macromolecules were in-depth analyzed via size exclusion chromatography (SEC) and nuclear magnetic resonance (NMR) spectroscopy. Additionally, SEC hyphenated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Apart from the chain growth polymerization systems, photo‐induced step growth polymerizations are also emerging as an increasingly attractive topic in polymer synthesis. Various photoreactions or photoinduced reactions, such as thiol‐ene reaction,9 photodimerization of cinnamates or coumarinates,10 photodimerization of 2‐furanacrylates,11 photoinduced electron transfer of iodonium salt,12 light induced nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC),13 UV‐light induced Diels–Alder reaction,14 etc., have been used for step growth polymerizations. In addition, AB‐type of monomers possessing aliphatic hydroxyl and photo labile benzodioxinones (as masked COOH) was also used for the synthesis of oligo polyester as a demonstration of the concept of photo induced step growth polymerization 15.…”
Section: Reaction Conditions and Results Of The Polymerizations Throumentioning
confidence: 99%
“…Apart from the chain growth polymerization systems, photo‐induced step growth polymerizations are also emerging as an increasingly attractive topic in polymer synthesis. Various photoreactions or photoinduced reactions, such as thiol‐ene reaction,9 photodimerization of cinnamates or coumarinates,10 photodimerization of 2‐furanacrylates,11 photoinduced electron transfer of iodonium salt,12 light induced nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC),13 UV‐light induced Diels–Alder reaction,14 etc., have been used for step growth polymerizations. In addition, AB‐type of monomers possessing aliphatic hydroxyl and photo labile benzodioxinones (as masked COOH) was also used for the synthesis of oligo polyester as a demonstration of the concept of photo induced step growth polymerization 15.…”
Section: Reaction Conditions and Results Of The Polymerizations Throumentioning
confidence: 99%
“…[ 16–21 ] By taking advantage of the advanced state of the conventional approaches, recent research interest in synthetic polymer chemistry is directed to adapt photoinduced reactions to step‐growth polymerization. Generally applied light induced strategies include cycloaddition [ 17,18 ] and selected organic reactions [ 19–22 ] or consequential electron transfer and radical coupling processes. The latter can be achieved by the use of conjugated aromatic structures as monomers and onium salts with appropriate oxidation potentials and non‐nucleophilic counter ions as oxidants.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the high reactivity and short lifetimes of photogenerated thioaldehydes, as well as the complex nature of photoinduced MCPs, an in‐depth understanding of the relationship between the synthetic conditions as well as product yield and purity is critical to successfully develop a robust visible‐light‐induced MCP methodology . Our research team has recently demonstrated that qualitative stochastic or kinetic Monte Carlo ( k MC) screening is indispensable in order to understand complex reaction mechanisms and for controlling selectivity toward a targeted product .…”
Section: Methodsmentioning
confidence: 99%